Duração razoável da investigação criminal: uma garantia fundamental do investigado - Nunes, Marcelo Alves (2013)
The proposition of constitutional guarantees in the criminal investigation stage is undoubtedly a significant progress in building a more ethical and fairer criminal case, consistent with republican values embodied in the Constitution of 1988. Thus, as an Estate institution, the Judicial Police has been ideologically remodeled, assuming a more guaranteed conformation in this constitutionalist era of law. This is because, in the early stage of the police investigation, the investigated might suffer serious restrictions on their nuclear legal heritage, as an example of dignity, freedom, intimacy and equity. Indeed, the choice of the legislature by the rule of non-term research officer [not only] demands immediate review, since the lack of regulatory control over the investigative acts fosters abuse of the Estate-police rather than expensive state values of the human person. As a reaction, the guarantee of reasonable duration of administrative procedures, constitutionally erected a fundamental right by EC 45/2004 (CF, art. 5th, inc. LXXVIII), points to the urgent need for critical revisiting of the criminal investigation, taken as a whole, since the delay in the completion of the procedure exacerbates feelings of distress and unfairly stigmatizes the investigated person, on whom an anticipated punishment, that cannot be confirmed by the State court, in a subsequent procedural step of the persecution criminis. Using the timing of the criminal investigation as its centerpiece, this study was initiated, from elementary concepts, positive legislation (ordinary and constitutional), the case law, the phenomenon of constitutionalization of law and specialized doctrine. In the exploration of the object of knowledge, related juridical aspects of sensitive relevance to the subject have not been left aside, especially the unintended consequences of investigation for the penal action, the possible defenses of the subject of prosecution, and the liability of the State and its agents, complementing and enriching excessively theoretical arguments submitted to reflection.